Peran Dinas Sosial dalam Meningkatkan Kemandirian Anak Jalanan Melalui Pelatihan Keterampilan Potong Rambut di Kabupaten Situbondo - Zaidah, Ita Khulfatuz; Imsiyah, Niswatul; Hasan, Fuad (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
This research aims to describe the role of Social Service in improving independence of street kids through haircut training. This research uses a qualitative research approach. The research site is at the Social Service of Situbondo Regency using the purposive area technique. The technique for determining informants is using purposive sampling. Data collection techniques were carried out using interview, observation, and documentation methods. The data collection instrument is the researcher himself who is referred to as the human instrument. The technique of checking the validity of the data uses a credibility test, namely the extension of participation, persistence of observation, triangulation of sources and triangulation of methods. The data analysis technique uses the theory of Miles and Huberman, namely data collection, data reduction, data presentation of data verification. The results of the research conducted indicate that the Department of Social Affairs plays a role as a companion, mentor, coach, and promoter so that they can make changes and increase emotional independence, economic independence, intellectual independence, and social independence in street kids. Keywords: The Role of Social Services, Independence, Street Kids.